2015
DOI: 10.1523/jneurosci.4685-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Model ofOPRM1(A118G) Polymorphism Increases Sociability and Dominance and Confers Resilience to Social Defeat

Abstract: A single nucleotide polymorphism (SNP) in the human -opioid receptor gene (OPRM1 A118G) has been widely studied for its association in drug addiction, pain sensitivity, and, more recently, social behavior. The endogenous opioid system has been shown to regulate social distress and reward in a variety of animal models. However, mechanisms underlying the associations between the OPRM1 A118G SNP and these behaviors have not been clarified. We used a mouse model possessing the human equivalent nucleotide/amino aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 50 publications
2
28
0
Order By: Relevance
“…In humans, adult carriers of the A118G OPRM1 polymorphism show less avoidance of affectionate relationships and increased capacity to experience social reward (Troisi et al , ), whereas child carriers display improved relationships, better resilience to aversive parental care and enhanced responses to facial expression of social and emotional stimuli (Copeland et al , ; Troisi et al , ; Bertoletti et al , ). Consistent with this, A118G OPRM1 knock‐in mice exhibit increased social interaction, dominance and protection from social defeat (Mague et al , ; Briand et al , ). Similarly, the C77G polymorphism in macaques, equivalent to the human A118G polymorphism, results in higher affiliative behaviour in mothers and infants (Barr et al , ; Higham et al , ).…”
Section: Role Of μ Receptors Under Neutral/positive Social Conditionsmentioning
confidence: 72%
“…In humans, adult carriers of the A118G OPRM1 polymorphism show less avoidance of affectionate relationships and increased capacity to experience social reward (Troisi et al , ), whereas child carriers display improved relationships, better resilience to aversive parental care and enhanced responses to facial expression of social and emotional stimuli (Copeland et al , ; Troisi et al , ; Bertoletti et al , ). Consistent with this, A118G OPRM1 knock‐in mice exhibit increased social interaction, dominance and protection from social defeat (Mague et al , ; Briand et al , ). Similarly, the C77G polymorphism in macaques, equivalent to the human A118G polymorphism, results in higher affiliative behaviour in mothers and infants (Barr et al , ; Higham et al , ).…”
Section: Role Of μ Receptors Under Neutral/positive Social Conditionsmentioning
confidence: 72%
“…Mice possessing the equivalent SNP (A112G) have decreased MOPR expression and morphine-evoked behaviors, altered GTPγS binding to the MOPR and downstream intracellular signaling cascades, and sex-specific deficits in morphine reward (Knapman et al, 2014; Mague et al, 2009; Wang et al, 2014; Wang et al, 2012). Additionally, recent studies in humans possessing the A118G SNP (Troisi et al, 2012; Way et al, 2010; Way et al, 2009) and in this mouse model of the A118G SNP (Briand et al, 2015) have shown in parallel that this SNP may have important ramifications for more complex behaviors, such as stress resiliency, which would also impact relapse behaviors in addiction. However, it has not been determined whether these effects result from decreased receptor availability or altered receptor function.…”
Section: Introductionmentioning
confidence: 89%
“…1A). In addition, it has been shown previously that the G allele is associated with an increase in home-cage dominance and increased motivation for nonaggressive social interactions (Briand et al, 2015); and it has also been shown that G-allele carrier mice have attenuated analgesic, anxiolytic, and hyperlocomotive effects from buprenorphine (Browne et al, 2017). In the humanized Oprm1 A118G mouse model, it has been shown that the effects of opioid antagonism on alcohol reward and consumption are affected (Bilbao et al, 2015).…”
Section: Behavioral Alterations In Rodent Models Of Oprm1 A118g Snpsmentioning
confidence: 97%
“…A loss of function in the minor allele caused differential outcomes, which might account for the different reward behaviors induced by drugs of abuse ( Fig. 1A) (Ramchandani et al, 2011;Bilbao et al, 2015;Robinson et al, 2015;Zhang et al, 2015;Browne et al, 2017) or other types of behavior (Briand et al, 2015).…”
Section: Impact Of Oprm1 A118 Gene Variant (N40d Mors) On Synaptic Rementioning
confidence: 99%
See 1 more Smart Citation